Model-based analyses reveal insular population diversification and cryptic frog species in the Ischnocnema parva complex in the Atlantic forest of Brazil - Gehara, Marcelo; Barth, Adriane; Oliveira, Eliana Faria de; Costa, Marco Antonio; Haddad, Célio Fernando Baptista [UNESP]; Vences, Miguel (Elsevier, 2017)
The Atlantic Forest (AF) of Brazil has long been recognized as a biodiversity conservation hotspot. Despite decades of studies the species inventory of this biome continues to increase with the discovery of cryptic diversity and the description of new species. Different diversification mechanisms have been proposed to explain the diversity in the region, including models of forest dynamics, barriers to gene flow and dispersal. Also, sea level change is thought to have influenced coastal diversification and isolated populations on continental islands. However, the timing and mode of diversification of insular populations in the AF region were rarely investigated. Here, we analyze the phylogeography and species diversity of the small-sized direct-developing frog Ischnocnema parva. These frogs are independent from water bodies but dependent on forest cover and high humidity, and provide good models to understand forest dynamics and insular diversification. Our analysis was based on DNA sequences for one mitochondrial and four nuclear genes of 71 samples from 18 localities including two islands, São Sebastião, municipality of Ilhabela, and Mar Virado, municipality of Ubatuba, both in the state of São Paulo. We use molecular taxonomic methods to show that I. parva is composed of six independently evolving lineages, with the nominal I. parva likely endemic to the type locality. The time-calibrated species tree shows that these lineages have diverged in the Pliocene and Pleistocene, suggesting the persistence of micro-refuges of forest in the AF. For the two insular populations we used approximate Bayesian computation to test different diversification hypotheses. Our findings support isolation with migration for São Sebastião population, with ∼1 Mya divergence time, and isolation without migration for Mar Virado population, with ∼13 Kya divergence time, suggesting a combination of different processes for diversification on AF islands.
Keywords: ABC; Amphibia; Brachycephalidae; Cryptic diversity; Insular diversification; Species delimitation